O impacto do programa do leite na vda familiar dos beneficiários do Rio Grande do Norte - Natal - Cruz, Taís Soares (2008)
This present study aims to identify and evaluate the impacts caused by the state Programa do Leite in the familiar life of the ones that get this benefit in Natal, from 2003 to 2008. The interviews were done in the four areas of the city and show the high level of poverty of the ones registered in the benefit. The introduction of the families in the program changed their habits. The study also shows the fragility of the poor population inside social welfare works like this one. Some of these programs become permanent by the politicians and by the lack of economic independence of the ones that get the benefit, causing much more dependence of these people on the social program